Simulation and optimization of non-isothermal compressible flow through large-bore two-stroke cycle natural gas transmission engines - Grauer, Diana Kathryn (Kansas State University, 2010)
This work includes a thermodynamic analysis of a large-bore two-stroke cycle engine air management system, resulting in the development of new software, for the purpose of analyzing: 1) the cylinder-to-cylinder distribution of charge air, 2) pollutant emission concentrations, and 3) energy availability to the turbocharger turbine. During the course of the thermodynamic analysis, four new algorithms were developed: 1. Charge Air Integrated Manifold Engine Numerical Simulation (CAIMENS), 2. Turbocharged-Reciprocating Engine Compressor Simulation (T-RECS) Nitrogen Oxide Kinetic Model, 3. T-RECS Carbon Monoxide Kinetic Model, and 4. Exhaust Manifold Design Software (EMDS). The EMDS, which integrates the three previously developed algorithms, can forecast pulsation and possible unbalanced air delivery and interference within the intake system and simulates energy release and pollutant emission formation during and just after the combustion event. Specifically, the EMDS outputs a transient spatial and temporal distribution of pressure and temperature within the engine exhaust stream. Beyond the development of the four engine characterization algorithms, an air flow balancer (AFB) was designed using data from the CAIMENS algorithm. This AFB as part of an overall Active Air Control system was used to balance the cylinder-to-cylinder distribution of air by the engine air management system and reduce total engine pollutant emission production.
Keywords: Engine; Model; Simulation; Optimization; Pollutant; Emission; Engineering, Mechanical (0548)